Scientific Committee guidance on appraising and integrating evidence from epidemiological studies for use in EFSA's scientific assessments - EFSA Scientific Committee; Simon More; Vasileios Bampidis; Diane Benford; Claude Bragard; Antonio Hernandez‐Jerez; Susanne Hougaard Bennekou; Konstantinos Koutsoumanis; Claude Lambré; Kyriaki Machera; Ewen Mullins; Soren Saxmose Nielsen; et al. (EFSA Journal, 2024)
Abstract EFSA requested its Scientific Committee to prepare a guidance document on appraising and integrating evidence from epidemiological studies for use in EFSA's scientific assessments. The guidance document provides an introduction to epidemiological studies and illustrates the typical biases, which may be present in different epidemiological study designs. It then describes key epidemiological concepts relevant for evidence appraisal. This includes brief explanations for measures of association, exposure assessment, statistical inference, systematic error and effect modification. The guidance then describes the concept of external validity and the principles of appraising epidemiological studies. The customisation of the study appraisal process is explained including tailoring of tools for assessing the risk of bias (RoB). Several examples of appraising experimental and observational studies using a RoB tool are annexed to the document to illustrate the application of the approach. The latter part of this guidance focuses on different steps of evidence integration, first within and then across different streams of evidence. With respect to risk characterisation, the guidance considers how evidence from human epidemiological studies can be used in dose–response modelling with several different options being presented. Finally, the guidance addresses the application of uncertainty factors in risk characterisation when using evidence from human epidemiological studies.